A frequency response model matching method for PID controller design for processes with dead-time. (March 2015) - Anwar, Md Nishat; Pan, Somnath
Abstract: In this paper, a PID controller design method for the integrating processes based on frequency response matching is presented. Two approaches are proposed for the controller design. In the first approach, a double feedback loop configuration is considered where the inner loop is designed with a stabilizing gain. In the outer loop, the parameters of the PID controller are obtained by frequency response matching between the closed-loop system with the PID controller and a reference model with desired specifications. In the second approach, the design is directly carried out considering a desired load-disturbance rejection model of the system. In both the approaches, two low frequency points are considered for matching the frequency response, which yield linear algebraic equations, solution of which gives the controller parameters. Several examples are taken from the literature to demonstrate the effectiveness and to compare with some well known design methods. Highlights: An approximate frequency response model matching method for PID controller is presented. The presented method is applicable to a variety of integrating processes (First order plus dead-time, Second order plus dead-time, Higher order with dead-time, inverse response). Two approaches are proposed for integrating process. In one approach, double feedback loop is considered and in another approach, load-disturbance rejection is considered. Two low frequency points are required for matching the frequency response and a criterion is provided for choosing such two frequency points. Involve with solution of linear algebraic equations and the computation is very minimum.